The Influence of Ethical Leadership, Organizational Justice, and Positive Work Environment on Organizational Citizenship Behavior of Employees of Restaurant Service Companies in Yogyakarta (International Journal of Economics and Management Research, 2026)
This study aims to examine the effect of ethical leadership, organizational justice, and a positive work environment on organizational citizenship behavior (OCB) of employees in a restaurant service company in Yogyakarta. Using a quantitative approach, this study involved 150 randomly selected employees and collected data through questionnaires. The data obtained were analyzed using multiple linear regression analysis. Results: ethical leadership has a significant positive effect on OCB (p < 0.05), indicating that ethical behavior demonstrated by leaders can increase OCB among employees. Likewise, organizational justice has a positive and significant effect on OCB (p < 0.05), indicating that employees who feel justice in the organization tend to demonstrate citizenship behavior. Furthermore, a positive work environment is also proven to have a significant effect on OCB (p < 0.05), where a safe, comfortable, and supportive working atmosphere contributes to increased citizenship behavior. The contribution of the study is in the development of OCB theory in the restaurant sector and provides practical recommendations that can be used by companies to improve employee loyalty and performance.